Analysis of Leading Metal (Pb) and Cadmium (Cd) Content Green Shells (perna viridis L.) in the Kreneng Market - A. A. Istri Mirah Dharmadewi (Journal of Sustainable Development Science, 2020)
This research was conducted to determine the content of heavy metals lead (Pb) and Cadmium (Cd) in green shells circulating in the kreneng market. Samples of green shells were taken from the kreneng market, Bali. Then analysis of the content of lead (Pb) and Cadmium (Cd) in the Analytical Laboratory of Udayana University. Samples of green mussels (Perna viridis L.) Were opened from the shell to take the meat. Furthermore, the sample is mashed by chopping and pounding and put into erlenmeyer. Each sample was given 3 repetitions using the factorial pattern RAL. Then with a wet ashing process (wet destruction). The results showed that the heavy metal content of lead and cadmium in green mussels (Perna viridis L.) Exceeded the maximum limit of heavy metal contamination. The heavy metal content of lead (Pb) shellfish taken at the Kreneng Market is 29.595 mg / kg while the heavy metal content of cadmium (Cd) taken at the Kreneng market is 3.41 mg / kg the result of the heavy metal content analyzed exceeds the predetermined by the Food and Drug Supervisory Agency (BPOM).